Antimicrobial resistance analysis of non-typhoidal Salmonella in porcine from northern Vietnam - Clark, E. (London School of Hygiene and Tropical Medicine, 2018)
Background Non-typhoidal Salmonella spp. (NTS) causing Salmonellosis remains a significant health burden in both developing and developed countries. Due to overcrowded hospitals and a lack of adequate diagnostic testing, Vietnam is a hotspot for drug resistance. Pork accounts for over 70% of total meat consumed within Vietnam, and contamination with NTS remains high. This study aimed to analyse the patterns of NTS serotypes and AMR of strains between 2014/5 to 2018 and also to determine whether the Colistin resistance seen in the 2014/5 study was caused by mcr-1. Methods To determine the presence of mcr-1, strains from a previous study, PigRISK 2014/5 were selected. The serotype was checked following the Kauffmann and White scheme, and Colistin antimicrobial resistance (AMR) performed using both disc diffusion and broth microdilution. Polymerase chain reaction (PCR) was used to determine the presence of mcr1. Samples representing 2018 were collected as part of the SafePORK study and processed for NTS isolation, serotyping and AMR for 12 antimicrobials. Results In the PigRISK strains, mcr-1 was not identified on either the chromosome or plasmid. From analysing serotypes and AMR between 2014/5 and 2018, a significant increase of NTS prevalence was observed from 44.7% to 78.6%. Antimicrobial resistance also remained high, and the number of strains showing multidrug resistance had increased between studies. Conclusion This study was limited to determining the presence of one gene causing Colistin resistance, further work is required to identify the exact cause of observed resistance. The collection of samples representing 2018 was limited to one province, one sample type and one section of the pork value chain. To aid comparison, it would be necessary to obtain a variety of samples. This study demonstrated why the control of antimicrobials within the agriculture sector is essential for preventing resistance, and subsequently transmission to humans.